2016
DOI: 10.1530/ec-16-0010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 68Ga-DOTANOC PET/CT and contrast-enhanced CT in localisation of tumours in ectopic ACTH syndrome

Abstract: BackgroundLocalising ectopic adrenocorticotrophic hormone (ACTH) syndrome (EAS) tumour source is challenging. Somatostatin receptor-based PET imaging has shown promising results, but the data is limited to case reports and small case series. We reviewed here the performance of 68Ga-DOTANOC positron emission tomography (PET)/computed tomography (CT) and contrast-enhanced CT (CECT) in our cohort of 12 consecutive EAS patients.Materials and methodsRetrospective data analysis of 12 consecutive patients of EAS pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
2
12
0
2
Order By: Relevance
“…series (4,7,13,14,23). In our study, a quarter of patients with EAS remained occult at the last available follow-up, as recently reported in a series with similar diagnostic approach (14).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…series (4,7,13,14,23). In our study, a quarter of patients with EAS remained occult at the last available follow-up, as recently reported in a series with similar diagnostic approach (14).…”
Section: Discussionsupporting
confidence: 81%
“…CT detected 90% of NETs in overt EAS, whereas 68 Ga-SSTR-PET/CT identified 70% of cases, without reporting false-positive imaging, resulting useful to increase the specificity of the suggestive CT-positive lesions. In this series, the only EAS not detected with conventional imaging remained occult also after the 68 Ga-SSTR-PET/CT (13). In a recent multicenter study, Wannachalee et al reported in 28 patients that 68 Ga-SSTR-PET/CT is sensitive to detect primary and metastatic neoplasms in EAS and to identify occult tumours after other type of imaging (in 65% of cases), achieving a significant clinical impact in the diagnostic-therapeutic management in the majority of patients (14).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Before prescribing additional imaging procedures, we strongly suggest a second careful examination of the thoracic CT-scan, which is the main source of occult EATs, ideally by several radiologists, to limit the risk of false negatives. Elsewhere, false positives on CT have been described in 3.6% of cases (149,155), a finding that emphasizes the importance of using an appropriate CT protocol and the experience of the radiologist to limit the frequency of thoracic lures. Additionally, it should be emphasized that imaging of the thorax in the search for an EAT may be particularly complex in patients with a pulmonary embolism or infection (see previous section).…”
Section: (2) First-line Imaging Proceduresmentioning
confidence: 99%